Impacto independente do diabetes na mortalidade de pacientes acompanhados em uma coorte hospitalar no Sul do Brasil - Watte, Guilherme (Universidade do Vale do Rio dos Sinos, 2013)
It is known that globally, 6% of deaths are caused by hyperglycemia, with 83% of these deaths occurring in low- and middle-income countries (WORLD HEALTH ORGANIZATION, 2009). Mortality rates among adults with heart disease and diabetics are 2 to 4 times higher than those for individuals without diabetes (NATIONAL DIABETES INFORMATION CLEARINGHOUSE, 2010). The relative risk of mortality when comparing diabetics and non-diabetics as an independent mortality factor is increased by 1.5 to 2 times during the hospital stay (ALMDAL et al., 2004). Cardiovascular diseases currently represent the largest cause of death in the world (GAZIANO et al., 2010; WORLD HEALTH ORGANIZATION, 2009), even becoming the main causes of death and hospitalization in people with diabetes (BERTONI et al., 2002; ROGER et al., 2011). The estimated value for healthcare spending in relation to diabetes was 376 billion dollars in 2010 and with the projection in 2030 to 490 billion dollars for everyone (ZHANG et al., 2010).
Keywords: Diabetes mellitus; Mortalidade; Estudos de coorte; Fatores de risco; Mortality; Cohort studies; Risk factors; ACCNPQ::Ciências da Saúde::Saúde Coletiva